2019
DOI: 10.22219/jiz.v2i2.9911
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception toward Social Media Assisted Language Learning (SMALL) for Arabic Learning

Abstract: The aims of this research were to determine the perception of students of Arabic Language Department towards the use of social media in teaching Arabic language and determine social media often used by students to help in the process of teaching Arabic language. This study used social anthropology approach in qualitative research because this study focusses on student’s perceptions towads mobile as their assistant for learning Arabic. The subject of study are 32 Arabic language education students at the State … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…The results of the above study differ from the conclusions of Abdullahi et al who concluded that students achieve high results in learning Arabic by using the web (Abdullahi et al, 2018). The results of this study also contradict the conclusions of Sari & Hasibuan who said that social media can improve students' skills (Sari & Hasibuan, 2019;Djumabaeva & Kengboyeva, 2021). While the results of this study indicate that students and lecturers' responses to learning Arabic as a whole show low Arabic listening skills.…”
Section: Students and Lecturers' Perceptions Of The Quality Of Online Arabic Learning Outcomescontrasting
confidence: 91%
“…The results of the above study differ from the conclusions of Abdullahi et al who concluded that students achieve high results in learning Arabic by using the web (Abdullahi et al, 2018). The results of this study also contradict the conclusions of Sari & Hasibuan who said that social media can improve students' skills (Sari & Hasibuan, 2019;Djumabaeva & Kengboyeva, 2021). While the results of this study indicate that students and lecturers' responses to learning Arabic as a whole show low Arabic listening skills.…”
Section: Students and Lecturers' Perceptions Of The Quality Of Online Arabic Learning Outcomescontrasting
confidence: 91%
“…Another study conducted by Fosu et al [61] confirmed similar findings. A study conducted by Sari & Hasibuan [62] regarding student perceptions of social networks in learning Arabic showed that social networks enhance language expertise, make education more inspiring, and transform student views on language learning. A study conducted by Balliammanda [15] on the use of mobile technology in Oman by school students revealed that learners felt uncomfortable when they forgot to carry their hi-tech devices.…”
Section: -3-prospective Teacher Perceptions Of Digital Network Sites ...mentioning
confidence: 99%
“…, 2019). Similarly, a survey of Arabic language students suggested that they perceive social media as improving language skills, making learning more interesting and changing their perspective on language learning (Sari and Hasibuan, 2019). Despite the many recent negative news items about the impact of social media use and considering the impact of the COVID-19 pandemic, students continue to perceive positive impacts of social media for learning.…”
Section: Literature Reviewmentioning
confidence: 99%